Language differences as an access barrier for Xhosa speaking patients at a children's hospital in Cape Town - Levin, Michael (Division of Paediatric Medicine, 2024)
The research documented in this thesis was conducted between November 2002 and March 2003. Rationale for the study. A problem faces many health professionals - that of communication between ourselves and patients who may differ from us in terms of the language spoken, educational level, medical knowledge, models of illnesses, socio-economic status, race and power.